2014
DOI: 10.3109/00016489.2014.892631
|View full text |Cite
|
Sign up to set email alerts
|

Myosin VIIa and otoferlin in cochlear inner hair cells have distinct response to ototoxic exposure

et al.

Abstract: Lower dose treatment: There were no significant differences among the control (day 0), and 4, 7, and 14 days after the ototoxicity exposure (p > 0.05). Dose-dependent gentamicin treatment: There were no significant differences among the control, 100, 200, and 300 mg/kg groups after the ototoxicity exposure (p > 0.05). In contrast, we found an altered expression of otoferlin in IHCs among the control (day 0), and 4, 7, and 14 days of exposure, when the mice were exposed to gentamicin ototoxicity (p > 0.05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…RIBEYE has been widely used as a marker for the specific presynaptic structure of ribbon synapse, and this key structural protein plays a critical role in ribbon synaptic formation and/or organization [22]. It, therefore, seems likely that the increases in number of synapses may reflect the enhancement in synaptic efficiency under physiological conditions [17]. To some extent, the changes of synaptic efficiency induced by IR in our study may not cause significant hearing threshold elevations.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…RIBEYE has been widely used as a marker for the specific presynaptic structure of ribbon synapse, and this key structural protein plays a critical role in ribbon synaptic formation and/or organization [22]. It, therefore, seems likely that the increases in number of synapses may reflect the enhancement in synaptic efficiency under physiological conditions [17]. To some extent, the changes of synaptic efficiency induced by IR in our study may not cause significant hearing threshold elevations.…”
Section: Discussionmentioning
confidence: 88%
“…Also our study revealed that myosin VIIa expression in IHCs remained unchangeable, regardless of IR due to dietary iron overload. Myosin VIIa is involved in the regulation and trafficking of intracellular endocytotic or secretory vesicles, and is important for vesicle cycling of cochlear hair cells [17]. Besides, IR due to dietary iron overload did not disrupt prestin expression in the OHCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RIBEYE is the central synaptic ribbon protein both at a structural as well as at a functional level. Previous works demonstrated that RIBEYE has an important structural role in building the ribbon backbone [11]. The ribbon structure has been considered to facilitate the release and recycling of neurotransmitters, and is thus responsible for both quick responses to rapidly changing signals and long-lasting responses to continuous stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, only two adjacent images from serial scanning could overlap. After all the images were marked, the total number of spheres was obtained using the layer manager of 3Ds Max [11,12]. The channel was then switched to register red fluorescence spots indicating post-synapse PSD95 and merged spots in orange (colocalized pre-and post-synapse signals) were counted by the same method as described above.…”
Section: Immunohistology and Confocal Imagingmentioning
confidence: 99%